Determinan Minat Penggunaan E-payment Syariah Dimoderasi Literasi Keuangan Syariah - Ike Dwi Agustina; Feri Dwi Riyanto (ITB AAS INDONESIA Surakarta, 2023)
The potential for using e-payments is so large that it encourages people to meet the transaction needs of the Indonesian people by using sharia-based e-payments. Sharia e-payment has become a trend and is currently being discussed by people in Indonesia. This study aims to identify factors that can influence the interest of MSMEs in Malang City in using sharia e-payments with Islamic financial literacy as moderation. The research conducted is a quantitative research with a descriptive approach. The sample used was 108 respondents who are owners/top management of MSME owners in Malang City who have made transactions using sharia e-payments in the last 3 years. The data obtained was tested with Partial Least Square (PLS-SEM). The results show that financial self-efficacy has an effect on perceived usefulness and intention to use sharia e-payment, perceived security has a significant effect on perceived usefulness and perceived ease of use, perceived usefulness and perceived ease of use has an effect on intention to use sharia e-payment. Meanwhile, financial self-efficacy has no effect on perceived ease of us and perceived ease of use has no effect on perceived usefulness. Islamic financial literacy can moderate financial self-efficacy. But, not able to moderate perceived security, perceived usefulness, and perceived ease of use.